2019
DOI: 10.1111/iej.13161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blue thermal treatment on endodontic instruments and apical debris extrusion during retreatment procedures

Abstract: Aim To determine the effect of blue thermal treatment on Reciproc (VDW, Munich, Germany) endodontic instruments and the amount of apically extruded debris during retreatment procedures. Methodology Thirty extracted mandibular molar teeth having mesial roots with a degree of curvature less than 20° and having an initial apical size equivalent to a size 10 K‐file were selected. The mesial roots of the teeth were removed from the cementoenamel junction to obtain a 15‐mm root length. The mesiobuccal canals were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
(62 reference statements)
2
14
0
1
Order By: Relevance
“…Many recent investigations performed with micro-CT technique but different NiTi instruments confirmed that the different retreatment technique is not able to completely remove debris of filling materials [ 8 , 17 , 18 ]. The results of the present study are in the same directions of previous investigations made with micro-CT and other methods on different NiTi instruments [ 10 , 19 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 86%
“…Many recent investigations performed with micro-CT technique but different NiTi instruments confirmed that the different retreatment technique is not able to completely remove debris of filling materials [ 8 , 17 , 18 ]. The results of the present study are in the same directions of previous investigations made with micro-CT and other methods on different NiTi instruments [ 10 , 19 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 86%
“…Recently, there is a tendency to perform apical extrusion studies focusing on root canal preparation systems with innovative manufacturing properties (Al‐Omari et al, 2021; Bürklein et al, 2021; Doganay Yildiz & Arslan, 2019; Duzgun et al, 2021; Elashiry et al, 2020; Mustafa et al, 2021; Uslu et al, 2018). These systems with different designs, alloy treatments and instruments which convert their phases at body temperature are being investigated in terms of extrusion.…”
Section: Review: Different Techniques To Evaluate the Amount Of Extru...mentioning
confidence: 99%
“…There are some drawbacks associated with the method, which necessitates the extrapolation of results with some caution despite all efforts for the standardization of samples. Firstly, the experimental model does not allow the simulation of the presence of vital pulp tissue or periapical tissues which may serve as barriers controlling the amount of extrusion under in vivo conditions (de Deus et al, 2014; Doganay Yildiz & Arslan, 2019; Ferraz et al, 2001; Kfir et al, 2018; Parirokh et al, 2012; Yeter et al, 2013). It has been reported that the lack of vital pulp tissue or necrotic tissues that may remain within lateral canals and apical ramifications could affect the results of laboratory studies (Topcuoglu et al, 2016b).…”
Section: Review: Different Techniques To Evaluate the Amount Of Extru...mentioning
confidence: 99%
“…Reciproc R25 instrument has a 0.25 mm apical size, 0.08 taper and S‐shaped cross‐sectional design (10). Reciproc instruments have been suggested for canal shaping and retrieval of canal fillings (11). Several studies have reported its superior shaping ability during root canal preparation (9) and retreatment (10,12) compared to conventional NiTi.…”
Section: Introductionmentioning
confidence: 99%